Impact of Total Quality Management (TQM) on Operational Performance of Ethiopian Pharmaceutical Manufacturing Plants - Dr. Seid Mohammed; Dr. Goulap Jagadish Brahma; Shegaw Aderaw (International Journal of Engineering and Management Research, 2019)
The purpose of this study is to examine the impact of TQM system on the operational performance of the pharmaceutical manufacturing companies operating in Ethiopia. Data for this study is collected using self-administered questionnaires. The survey is carried out on 65 respondents drawn from 13 companies. Out of 65 questionnaires distributed among these companies, a total of 57 got returned. Through comprehensive literature review, seven critical success factors of TQM that are relevant to the pharmaceutical industry are identified. Correlation & regression analyses are used to investigate the relationship between TQM variables on the one side and common operational performance measures (Quality, Cost, and Delivery & Flexibility to volume) on the other side. The Correlation analysis reveals that there is strong relationship between TQM practices and operational performance among the pharmaceutical manufacturing companies. The outcome of regression analysis indicates that customer focus, process management, product design and people management have significant contribution to at least one of the operational performance measures. Top Management’s support, suppliers’ quality management and continuous improvement do not appear to contribute to higher levels of performance. This study offers pharmaceutical companies and their managers a better understanding of the relationship and impact that some of TQM elements have on the performance of their operations. Thus managers will get an opportunity to take better & more effective decisions in the implementation of TQM. This study can also guide organizations to prioritize the implementation of TQM based on the strategic importance of performance measures needed by them. The choice performance measure is based on the perceptions of managers and therefore, generalization of the observations may be made with caution.